Simple modules of the quantum double of the Nichols algebra of unidentified diagonal type ufo(7) - Andruskiewitsch, Nicolas (2018)
The finite-dimensional simple modules over the Drinfeld double of the bosonization of the Nichols algebra ufo(7) are classified.